2015
DOI: 10.1111/nmo.12512
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic nervous system dysregulation in irritable bowel syndrome

Abstract: IBS subjects display a significant reduction in α index, an established marker of cardiac baroreflex. ANS dysfunction appears to be involved in the pathophysiology of IBS and its assessment may open new perspectives for clinical management of patients suffering from IBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 55 publications
(63 reference statements)
5
42
0
2
Order By: Relevance
“…These results are consistent with the current pathophysiological knowledge of these functional disorders, although most of the research in this area focuses predominantly on IBS [5,6,8,10,28,29]. …”
Section: Discussionsupporting
confidence: 89%
“…These results are consistent with the current pathophysiological knowledge of these functional disorders, although most of the research in this area focuses predominantly on IBS [5,6,8,10,28,29]. …”
Section: Discussionsupporting
confidence: 89%
“…21 Some studies have demonstrated an altered autonomic function in IBS patients and suggest that IBS patients have increased sympathetic nervous system and cardiovascular activation. 22,23 The endothelin system seems to exert an increased vasoconstrictive and sympathoexcitatory role in conditions characterized cardiovascular risk such as hypertension. 15 Moreover, some studies demonstrated that ET-1 mediates smooth muscle contraction in GI tract.…”
Section: Discussionmentioning
confidence: 99%
“…3,[11][12][13] Recent evidence suggests that alterations in the brain-gut axis play an important role in IBS, 14,15 including altered sympathetic and parasympathetic activities of the autonomic nervous system (ANS). 16 Similarly, patients with IBS are known to have a higher occurrence of mood disturbances, anxiety, depression, somatization disorders, and psychological distress, 15,17 and the central nervous system (CNS) is believed to be involved in the concomitance of these conditions. 15,18,19 Heart rate variability (HRV) is a noninvasive measure of ANS activities.…”
Section: Introductionmentioning
confidence: 99%